Analisis Sintaksis Kāna wa-Akhawātuhā dalam Kitab al-‘Arabīyah li-al-Nāshi’īn - Ummi Hanik; Muhammad Afif Amrulloh (Universitas Negeri Jakarta, 2019)
This study aims to find out the forms of ism kāna and khabar kāna wa-akhwātuhā. This research is qualitative with a type of library research. Data collection techniques are using the documentation method, while data analysis techniques are using content analysis. The results of this study prove that in al-‘Arabīyah li-al-Nāshi’īn book, volume 4, there are 161 types of ism kāna, while khabar kāna totaling 84 are analyzed based on (1) The i‘rāb aspect and its form there are 38 ism kāna in the form of ism mabnī consisting of 28 ḍamīr mustatir jawāzān, 7 ḍamīr bāriz which are composed of ḍamīr muṭṭaṣil and 3 ism al-ishārah. Likewise, 46 ism kāna in the form of ism mu‘rab; 41 ism mufrad, 3 jam‘ al-taksīr, 1 ism tahnīyah and 1 asmā’ al-khamsah. As for the aspects of its type, there are 77 ism kāna in the form of mudhakkar and mu’annath, 63 consisting of mudhakkar and 14 consisting of mu’annath. (2) 84 khabar kāna consists of 38 khabar mufrad in the form of ism jāmid and ism mushtaq, 33 khabar in the form of fi‘l mudhari‘ and 13 khabar shibh al-jumlah in the form of jār majrūr. This study contributes to the development of studyng Arabic grammar which can be applied in the use of Arabic as in the book.